The Influence of Product Quality and Electronic Word of Mouth on Customer Loyalty in Skincare Products at Sociolla Cirebon - Indy, Ristalia; Aq, Pebi Yanti Nobu; Yusuf, Yusuf; Rahmadi, Rahmadi (International Journal of Business, Economics, and Social Development, 2025)
The skincare industry is undergoing a swift transformation, driven by advancements in active ingredients and technology, resulting in fierce competition as new brands emerge. In this digital landscape, product quality and Electronic Word of Mouth (e-WOM) serve as pivotal forces in cultivating customer loyalty. This study seeks to investigate the influence of these two factors on customer loyalty in skincare products available at Sociolla Cirebon. Employing a quantitative research method with an associative approach, the study surveyed 150 respondents selected through purposive sampling. Data collection was conducted via a structured questionnaire encompassing three principal dimensions: product quality, e-WOM, and customer loyalty. A series of statistical analyses were performed, including validity and reliability assessments, multicollinearity and heteroscedasticity tests, multiple linear regression analysis, partial significance testing (T-test), simultaneous significance testing (F-test), and the coefficient of determination (R²) test. The findings reveal that both product quality and e-WOM exert a significant and positive effect on customer loyalty, with an R² value of 0.943, indicating that these variables account for 94.3% of customer loyalty, while the remaining 5.7% is influenced by other factors. These results underscore the necessity of integrating superior product quality with a well-managed e-WOM strategy to fortify customer allegiance in an increasingly competitive market. Consequently, businesses should continuously enhance product quality and strategically utilize e-WOM to sustain and improve customer retention.